Transition Metal-Mediated C−C Single Bond Cleavage: Making the Cut in Total Synthesis - Wang, Brian (Angew Chem Int Ed Engl, 2020)
Transition-metal-mediated cleavage of C−C single bonds can enable entirely new retrosynthetic disconnections in the total synthesis of natural products. Given that C−C bond cleavage inherently alters the carbon framework of a compound, and that, under transition-metal catalysis, the generated organometallic or radical intermediate is primed for further complexity-building reactivity, C−C bond-cleavage events have the potential to drastically and rapidly remodel skeletal frameworks. The recent acceleration of the use of transition-metal-mediated cleavage of C−C single bonds in total synthesis can be ascribed to a communal recognition of this fact. In this Review, we highlight ten selected total syntheses from 2014 to 2019 that illustrate how transition-metal-mediated cleavage of C−C single bonds at either the core or the periphery of synthetic intermediates can streamline synthetic efforts.